EMPLOYEES' VIEWS ON THE WAYS OF MANAGING AND ORGANIZING WORK PROCESSES IN THE INSTITUTE FOR ANTI-RABIES PROTECTION - THE PASTEUR INSTITUTE, NOVI SAD - Gazibara, Dragana; Ključar, Marko; Stojišić, Andrea; Mijatović, Dragana; Banović, Pavle (HEALTH CARE, 2024)
-Management in healthcare plays a pivotal role in enhancing the operations of healthcare institutions, integrating technology, and developing human resources. The aim of our research was to examine the attitudes of employees in the Institute for anti-rabies protection - The Pasteur Institute, Novi Sad towards the organization itself, organizational climate (atmosphere and relations between employees, primarily managers and other members of the collective) and management.Methods: A survey was conducted among 19 employees, using the GoogleForms platform, employing a modified version of The Work Design Questionnaire, which includes 8 demographic questions about the respondent and 26 questions related to the research topic. Respondents, constituting 86.4% of the total of 22 employees, expressed their agreement with the statements using a scale with grades from 1 to 5.Results: The majority of respondents believe that functions, goals, and responsibilities within the Pasteur Institute, Novi Sad are clearly defined. The position of the employees is that there is room for increasing the participation of employees in decision-making.Conclusion: It is necessary to introduce a more participatory approach in the decision-making process in the institution and implement measures aimed at the maximum use of employees' abilities, improvement of communication and information of employees, involvement of employees in the decision-making process, strengthening of mutual trust and development of team spirit in order to improve the efficiency of the institution and achieve sustainable improvement of organizational climate and leadership work in the Pasteur Institute, Novi Sad.
Keywords: Healthcare Management; Organizational Structure; Employee Engagement; Organizational Climate